2007
DOI: 10.4314/ijard.v9i1.2656
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Jackbean (<i>Canavalia ensiformis</i> L.DC) Seed Meal as a Substitute for Fishmeal in diets for <i>Clarias gariepinus</i> (Burchell, 1822)

Abstract: Jackbean (Canavalia ensiformis) is an under-utilised novel legume with crude protein content and amino acid profile that make it a potential candidate in the tropics as substitute for fish meal in fish diets. This study assesses the potentials of Jackbean seed meal (JBSM) for partial replacement of fish meal in diets of Clarias gariepinus. Fishmeal in control diet was replaced progressively (10%,20%,40% and 60%) by raw JBSM, 30-and 60-minute boiled JBSM. Test fish in each tank were fed 3% of their biomass twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…However, the markedly presence of canavaline and saponin in C. ensiformis are also possible causes of reduced growth observed in this study. Osuigwe et al (2002Osuigwe et al ( , 2003Osuigwe et al ( , 2005 among other authors have previously reported the effect of canavaline which is thermostable, poisonous, alkaline aminoacid with a structural analogue of arginine (= lines 144, 145) no the performance of fish growth. , Akinbiyi (1992), and Abdo de la Parra et al (1998) had earlier reported that Clarias gariepinus can tolerate higher inclusion of raw C. ensiformis meal (11% level of inclusion) better than O. niloticus (5% level of inclusion).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the markedly presence of canavaline and saponin in C. ensiformis are also possible causes of reduced growth observed in this study. Osuigwe et al (2002Osuigwe et al ( , 2003Osuigwe et al ( , 2005 among other authors have previously reported the effect of canavaline which is thermostable, poisonous, alkaline aminoacid with a structural analogue of arginine (= lines 144, 145) no the performance of fish growth. , Akinbiyi (1992), and Abdo de la Parra et al (1998) had earlier reported that Clarias gariepinus can tolerate higher inclusion of raw C. ensiformis meal (11% level of inclusion) better than O. niloticus (5% level of inclusion).…”
Section: Discussionmentioning
confidence: 99%
“…However, lectin and canavaline were not markedly reduced using this processing method. Canavaline, has long been reported as a thermostable, poisonous, alkaline amino acid with a structural analogue of arginine (Osuigwe et al 2002;2003;. However, it could be rightly said that the duration of time used for toasting was too short to cause a marked reduction in saponin despite not been thermostable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent past, researches were mostly focused on the under-utilized plant proteins in fish diets. Prominent among which are soybean meal [8] [9], groundnut cake [10], Lima bean [11], Jackbean [12] [13], African Yam bean [14], Pigeon Pea [15]. Relatively, work on the use of other oilseeds residue such as sesame meal in warm water fish nutrition is limited [16].…”
Section: Introductionmentioning
confidence: 99%